New fatigue life design approach for metal sheets with discontinuities. (2020) - Algarni, Mohammed; Alashwal, May; Zwawi, Mohammed; Ghazali, Sami; Felemban, Bassem F.
Abstract: The existing references of Wöhler data curves (S-Nf fatigue life) for fully reversed cycling loading fail to incorporate the discontinuities effect on metal sheets fatigue life. Experimental results show that the discontinuities, i.e., holes and notches weaken metal sheets and reduce fatigue life. The notch fatigue strength reduction factor ( Kf ) cannot incorporate the discontinuity effect into the fatigue life prediction models. This paper investigates a new method to study the discontinuity effect on metals fatigue life by applying the Discontinuity Stress Triaxiality (DST) factor to fatigue life prediction models. Three discontinuity geometries were studied in order to investigate the different effect of different radius. A simulation using ABAQUS FEA was used to export the stress triaxiality at the notch root element. The results show that this new method can help in predicting fatigue life for high-strength metals and metals with sharp notches, unlike the Kf factor. Also, the theoretical results show good correlation with the experimental results.